Sodium tanshinone IIA sulfonate protects rat myocardium against ischemia-reperfusion injury via activation of PI3K/Akt/FOXO3A/Bim pathway - Zhang Mei-qi; Zheng Yue-liang; Chen Huan; Tu Jian-feng; Shen Ye; Guo Jun-ping; Yang Xiang-hong; Yuan Shu-ren; Chen Liang-zhong; Chai Jing-jie; Lu Jian-hong; Zhai Chang-lin (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the mechanisms underlying the protective effects of sodium tanshinone IIA sulfonate (STS) in an ischemia-reperfusion (I/R)-induced rat myocardial injury model. Methods: Male SD rats were iv injected with STS, STS+LY294002 or saline (NS) for 15 d. Then the hearts were subjected to 30 min of global ischemia followed by 2 h of reperfusion. Cardiac function, infarction size and area at risk were assessed. Cell apoptosis was evaluated with TUNEL staining, DNA laddering and measuring caspase-3 activity. In addition, isolated cardiomyocytes of neonatal rats were pretreated with the above drugs, then exposed to H2O2 (200 mol/L) for 1 h. Cell apoptosis was detected using flow cytometric assay. The levels of p-Akt, p-FOXO3A and Bim were examined with immunoblotting. Results: Compared to NS group, administration of STS (20 mg/kg) significantly reduced myocardial infarct size (40.28%±5.36% in STS group vs 59.52%±7.28% in NS group), and improved the myocardial function as demonstrated by the increased values of dp/dtmax, LVDP and coronary flow at different reperfusion time stages. Furthermore, STS significantly decreased the rate of apoptotic cells (15.11%±3.71% in STS group vs 38.21%±7.83% in NS group), and reduced caspase-3 activity to nearly a quarter of that in NS group. Moreover, STS significantly increased the phosphorylation of Akt and its downstream target FOXO3A, and decreased the expression of pro-apoptotic gene Bim. Co-treatment with the PI3K inhibitor LY294002 (40 mg/kg) partially countered the protective effects induced by STS treatment. In isolated cardiomyocytes, STS exerted similar protective effects as shown in the ex vivo I/R model. Conclusion: STS pretreatment reduces infarct size and improves cardiac function in an I/R-induced rat myocardial injury model via activation of Akt/FOXO3A/Bim-mediated signal pathway.